RESPONSE OF STRAWBERRY (FRAGARIA ANANASSA)TO THE APPLICATION OF MICROBIAL INOCULANTS AND ORGANIC FERTILIZERS - SULIMAN, HUSSEIN MAMO; YOUSIF, SAMIRA HASSAN; YOUSIF, KURDISTAN HASSAN (Journal of Duhok University, 2020)
The present study was carried out during growing season of 2018-2019, in the wooden canopy of the College of Agricultural Engineering Sciences, University of Duhok, Kurdistan Region of Iraq, to investigate the influence of foliar spray of four concentrations of Urea (0, 0.5, 1 and 1.5 g.L -1 ) and inoculation the soil with Azotobacter at two concentrations (0 and 10 m.L -1 ) and their interaction on the vegetative growth properties and quality of strawberry plant cv. Rubygem. The results indicated that Urea and Azotobacter significantly increased vegetative growth (chlorophyll, fresh weight, leaf area, leaf number and dry weight) as well as fruit quality (fruit weight, fruit length and number of fruits) (15.4g, 5.58cm and 10.67) respectively as compared with untreated plants. The interaction between the studies factors varied in their effect on the traits. The best interaction was the interaction of Urea at concentration (1g.L -1 ) and Azotobacter at (10 m.L -1 ) which gave the highest values (45.17 SPAD, 15.84 g and 5.38g) respectively as compared with other plants.